Bladder urothelial carcinoma producing insulin‐like growth factor II: A case report. Issue 1 (20th September 2018) - Funada, Satoshi; Kita, Yuki; Okada, Yoshiyuki; Kobayashi, Takashi; Teramoto, Yuki; Shibuya, Shinsuke; Saito, Ryoichi; Murakami, Kaoru; Matsumoto, Keiyu; Yang, Feng; Dimitrov, Dimiter S; Inoue, Takahiro; et al.
Abstract : Introduction: Non‐islet cell tumor hypoglycemia is a rare paraneoplastic syndrome associated with tumors. Although it mainly occurs in solid tumors of mesenchymal and epithelial origin, but rarely also in hematopoietic and neuroendocrine origin. Case presentation: We describe a 65‐year‐old man with a muscle‐invasive bladder urothelial carcinoma, which rapidly progressed against systemic chemotherapy consisting of gemcitabine and cisplatin. Notably, the patient developed hypoglycemia at the terminal stage of the disease. Pathological diagnosis was giant cell urothelial carcinoma, which was strongly positive for insulin‐like growth factor‐II in immunohistochemistry. We established patient‐derived xenograft from insulin‐like growth factor‐II producing bladder urothelial carcinoma that caused non‐islet cell tumor hypoglycemia. Although we evaluated the efficacy of the neutralizing antibody, there was no statistically significant inhibitory effect on tumor growth. Conclusion: To the best of our knowledge, this is the first report of insulin‐like growth factor‐II‐producing urothelial carcinoma that have been recapitulated in a patient‐derived xenograft model.